Molecular detection of feline hemoplasmas and retroviruses in free-roaming and shelter cats within a university campus - Yamakawa, Ana Carolina [UNESP]; Haisi, Amanda [UNESP]; Kmetiuk, Louise Bach; Pellizzaro, Maysa; Mendes, Juliana Cristina Rebonato; Canavessi, Aurea Maria Oliveira; Ullmann, Leila Sabrina [UNESP]; Pessoa Araújo Júnior, João [UNESP]; Santos, Andrea Pires dos; Biondo, Alexander Welker (SAGE Publications, 2023)
Objectives: The aim of the present study was to assess the frequency of hemoplasma, feline immunodeficiency virus (FIV) and feline leukemia virus (FeLV) infections in cats living in an on-campus shelter and free-roaming cats within a university campus in Brazil. Methods: Blood samples were tested using quantitative PCR for hemoplasma, FIV and FeLV. Positive hemoplasma samples were sequenced. Associations between hemoplasma detection and living situation, sex, flea and/or tick parasitism, and coinfection with FIV and FeLV, were assessed using Fisher’s exact test and the respective odds ratios were calculated. Results: Overall, 6/45 (13.3%) cats tested positive: four (8.9%) were infected with ‘Candidatus Mycoplasma haemominutum’ and two (4.4%) with Mycoplasma haemofelis. All positive samples were from free-roaming cats (6/15; 40.0%) and had statistically significantly lower packed cell volumes (P = 0.037). Although 5/23 (21.7%) males and 1/22 (4.6%) females were positive, no statistically significant association between sex and hemoplasma infection was found (P = 0.19). Viral quantitative PCR (qPCR) was performed on 43/45 samples, among which 2/43 (4.7%) were positive for FIV and none for FeLV. Only one cat (2.3%) was coinfected with hemoplasma and FIV (P = 0.26). In addition, 4/6 (66.7%) cats that tested positive for hemoplasmas were infested by fleas (P = 0.0014) and/or ticks (P = 0.25). Conclusions and relevance: These results show that even if the free-roaming cat population is clinically healthy and has adequate access to food, it may present flea infestation and hemoplasma infection with lower packed cell volume values.
Keywords: Animal health; coinfection; feline immunodeficiency virus; hemotropic mycoplasma; molecular diagnosis